2012
DOI: 10.1002/chem.201102426
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Ru Catalyst for the Asymmetric Transfer Hydrogenation of Both Aromatic and Aliphatic Sulfinylimines

Abstract: A highly efficient Ru catalyst based on an achiral, very simple, and inexpensive amino alcohol ligand (2-amino-2-methylpropan-1-ol) has been developed for the asymmetric transfer hydrogenation (ATH) of chiral N-(tert-butylsulfinyl)imines. This complex is able to catalyze the ATH of both aromatic and the most challenging aliphatic sulfinylimines by using isopropyl alcohol as the hydrogen source. The diastereoselective reduction of aromatic, heteroaromatic, and aliphatic sulfinylketimines, including sterically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 99 publications
2
28
0
Order By: Relevance
“…Since those ligands have shown to give excellent results in the ruthenium-catalyzed asymmetric transfer hydrogenation of ketones [12][13][14][15][16][17][18][19] and N-sulfinylimines [38][39][40][41] in isopropyl alcohol, we decided to investigate if they could also be applied to the reduction of N-phosphinyl ketimines by the same methodology. One of the most noteworthy chiral β-amino alcohols in the ATH of both ketones and N-sulfinyl imines is cis-1-amino-2-indanol [50].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since those ligands have shown to give excellent results in the ruthenium-catalyzed asymmetric transfer hydrogenation of ketones [12][13][14][15][16][17][18][19] and N-sulfinylimines [38][39][40][41] in isopropyl alcohol, we decided to investigate if they could also be applied to the reduction of N-phosphinyl ketimines by the same methodology. One of the most noteworthy chiral β-amino alcohols in the ATH of both ketones and N-sulfinyl imines is cis-1-amino-2-indanol [50].…”
Section: Resultsmentioning
confidence: 99%
“…A slight improvement of both yield and enantioselectivity were observed when the initial temperature was −20 °C instead of 0 °C (Table 1, entry 12). Since in our previous studies concerning the ATH of N-(tert-butylsulfinyl)imines [38][39][40][41] we found that potassium tert-butoxide was a more convenient base than potassium hydroxide, we decided to evaluate the former in the ATH of phosphinylimine 1a and we obtained a further improvement, giving 87% yield and 82% ee (Table 1, entry 13). A decrease of the initial temperature to −40 °C slightly reduced both the yield and the enantiomeric excess (Table 1, entry 14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, highly enantiomerically enriched -branched primary amines are obtained in excellent yields by the diastereoselective reduction of a variety of sulfinylimines followed by desulfinylation of the nitrogen atom. 10 The N-(tert-butylsulfinyl)imines are prepared by reaction of stoichiometric amounts of the corresponding ketones and 2-methylpropane-2-sulfinamide in the presence of two equivalents of Ti(OEt) 4 under solventfree conditions. 11 The obtained imines 3 are reduced by asymmetric transfer hydrogenation using isopropyl alcohol as hydrogen source and, as a catalyst, a ruthenium complex bearing a commercially available simple achiralaminoalcohol: 2-amino-2-methylpropan-1-ol.…”
Section: Discussionmentioning
confidence: 99%